The authentic leader : using the Meisner technique for embracing the values of truthful leadership - Sparks, Royce (New York, NY : Routledge/Productivity Press, 2021)
"Using clear and simple exercises adapted for leadership development from the world-renowned Meisner Technique, The Authentic Leader will help you discover first-hand what it means to build your authentic leadership skills in a clear, technical way. Whether you are green in your career or at the head of a nation, an aspiring leader or an educator looking to use this material, this work develops and nourishes powerful leadership in unconventional, effective and dynamic ways"--
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Meisner, Sanford; Leadership -- Study and teaching; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Management